The Suitability Triad: Authenticity, Interest, and Need in High School Listening Instructions - Nungki Nurbani, Armelia (Journal of Applied Linguistics and English Education, 2025)
Although listening is one of skill appears in national examination, there is no audio recorded provided in BSE’s book. That is why many English teachers download the materials from the internet. In order to know the suitability quality of authentic listening materials used by teachers, one possible way to address the issue is doing suitability analysis of authentic listening materials that used by the teachers. Authentic listening materials that used by two Senior High English teachers were analyzed within two weeks when the teachers were teaching in each eleventh-grade class. There were six classes of eleventh grade. This research only focused on three aspects of suitability and interpreted whether the authentic materials used by teacher suit with the authenticity, students’ interest, and students’ needs or not. Teacher 1 only used songs in two different meetings. Teacher 2 used a video of cooking competition and parts of films. For suitability to the materials’ authenticity, both researcher and observer agreed that all of authentic listening materials used by teachers were suitable to the use of language in the world. For suitability to the students’ interest, the authentic listening materials that used by all teachers in meeting 1 were suitable to the students’ interest, and in meeting 2 were not suitable to the students’ interest. For suitability to the students’ needs, there is no authentic listening materials that requires all the students’ needs. In conclusion, although the teachers are aware the importance of using authentic listening materials, they still miss the importance of three aspects inside the materials’ suitability. It may be caused by less awareness in doing need analysis before making the lesson plan